Relative deprivation and incident functional disability among older Japanese women and men: prospective cohort study. Issue 6 (12th February 2009) - Kondo, N; Kawachi, I; Hirai, H; Kondo, K; Subramanian, S V; Hanibuchi, T; Yamagata, Z
Abstract : Background: A prospective observational study was conducted to test the hypothesis that relative deprivation was associated with incident physical or cognitive disability, independent of absolute income. Methods: Study subjects consist of 9463 non-disabled people aged 65+ years in the Aichi Gerontological Evaluation Study (AGES), Aichi prefecture, Japan. Baseline mail-in survey in 2003 gathered information on income, educational attainment, lifestyle factors (smoking, alcohol consumption and health check-up) and healthcare utilisation. Three-year incidence of disability was assessed through public long-term care insurance databases and resident registry. Results: A total of 7673 subjects (81%) with complete information were analysed. Our measure of relative deprivation was the Yitzhaki index across eight reference groups, which calculates the deprivation suffered by each individual as a function of the aggregate income shortfall for each person relative to everyone else with higher incomes in that person's reference group. Cox regression demonstrated that, after controlling for sociodemographic factors (including absolute income), the hazard ratio (and 95% confidence intervals) of incident physical/cognitive disability per one standard deviation increase in relative deprivation ranged from 1.13 (0.99 to 1.29) to 1.15 (1.01 to 1.31) in men and from 1.11 (0.94 to 1.31) to 1.18 (1.00 to 1.39) in women, depending on the definition of the reference group. Additional adjustment for lifestyle factors attenuated the hazard ratios to statistical non-significance. Conclusion: Relative deprivation may be a mechanism underlying the link between income inequality and disability in older age, at least among men. Lifestyle factors in part explain the association between relative deprivation and incident disability.